Impact of antigen specificity on CD4(+) T cell activation in chronic HIV-1 infection - Smith, Miranda Z (BioMed Central, 2013)
BACKGROUND: HIV infection induces chronic immune activation which is associated with accelerated disease progression; the causes of this activation, however, are incompletely understood. We investigated the activation status of CD4(+) T cells specific for chronic herpes viruses and the non-persistent antigen tetanus toxoid (TT) in HIV positive and HIV negative donors to assess whether persistent infections contribute to chronic CD4(+) T cell activation. METHODS: Untreated HIV(+) patients and healthy, aged matched controls were recruited and activation levels assessed and compared between cells specific for persistent and non-persistent antigens. Activation levels on antigen-specific CD4(+) T cells were measured by intracellular cytokine staining following in vitro stimulation with various recall antigens (CMV, EBV, HSV, VZV and TT) in conjunction with cell surface phenotyping. RESULTS: Activation levels of herpes virus-specific CD4(+) T cell populations, assessed by co-expression of CD38 and HLA-DR, were significantly elevated in HIV(+) individuals compared to normal controls and compared to TT-specific responses. In contrast, we found similar levels of activation of TT-specific CD4(+) T cells in HIV(+) and HIV(-) donors. CONCLUSIONS: These results show a disparate distribution of immune activation within CD4(+) T cell populations depending on their specificity and suggest that the elevated level of immune activation that characterizes chronic HIV infection may be influenced by the persistence of other antigens.